Duality for Knizhnik-Zamolodchikov and Dynamical Operators - Tarasov, Vitaly; Uvarov, Filipp (Symmetry, Integrability and Geometry: Methods and Applications, 2020)
We consider the Knizhnik-Zamolodchikov and dynamical operators, both differential and difference, in the context of the (glₖ,glₙ)-duality for the space of polynomials in anticommuting variables. We show that the Knizhnik-Zamolodchikov and dynamical operators naturally exchange under the duality.